2008
DOI: 10.1021/jp8003085
|View full text |Cite
|
Sign up to set email alerts
|

Order and Dynamics of a Liquid Crystalline Dendrimer by Means of 2H NMR Spectroscopy

Abstract: A complete Deuterium NMR study performed on partially deuterated liquid crystalline carbosilane dendrimer is here reported. The dendrimer under investigation shows a SmA phase in a large temperature range from 381 to 293 K, and its mesophasic properties have been previously determined. However, in this work the occurrence of a biphasic region between the isotropic and SmA phases has been put in evidence. The orientational order of the dendrimer, labeled on its lateral mesogenic units, is here evaluated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 59 publications
0
29
0
Order By: Relevance
“…Nuclear magnetic resonance (NMR) spectroscopy is a very effective method for studying the local dynamics. [3][4][5][6][7][8][9][10][11][12] Recent works 11,12 have demonstrated that one can address via NMR different shells of Frechet-type dendrimers and thus monitor their segment mobilities separately. In particular, one can differentiate between the inner and the terminal segments.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear magnetic resonance (NMR) spectroscopy is a very effective method for studying the local dynamics. [3][4][5][6][7][8][9][10][11][12] Recent works 11,12 have demonstrated that one can address via NMR different shells of Frechet-type dendrimers and thus monitor their segment mobilities separately. In particular, one can differentiate between the inner and the terminal segments.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the spectral shape of 2 H NMR spectra of liquid crystals provided an excellent and powerful method to investigate the supramolecular structure of liquid crystals, such as in frustrated phases (TGBA, TGBC* and so on) [24] and ferroelectric (SmC*) phases [25]. Dynamic properties, such as molecular reorientational diffusion, translational self-diffusion and collective motions are mainly investigated by specific NMR approaches, such as NMR diffusometry [26] and NMR relaxometry [27] (which requires specific equipment), or by analysing the spin-spin (T 2 ) and spin-lattice (T 1 ) relaxation times (mainly 1 H and 2 H) through specific models [28][29][30]. In few cases, for instance if molecules are distributed in not homogeneously aligned structures, 2D exchange NMR methods can also be applied [31].…”
Section: Nmr Basic Principles and Applications To Study Liquid Crystalsmentioning
confidence: 99%
“…Despite their spherical shape in solution or in the isotropic phase, LC dendrimers arrange in highly anisotropic structures when entering the LC mesophases. The microsegregation between the cores and the terminal units observed in smectic phases of carbosilane dendrimers, as well as the ordering properties of these LC dendrimers in the presence of external fields, were investigated by 2 H and 1 H NMR [76][77][78].…”
Section: … To Complex Liquid-crystalline Materialsmentioning
confidence: 99%